69 Gb/s DMT direct modulation of a Heterogeneously Integrated InP-on-Si DFB Laser - Rahim, Abdul; Abbasi, Amin; Sequeira André, Nuno; Katumba, Andrew; Louchet, Hadrien; Van Gasse, Kasper; Baets, Roel; Morthier, Geert; Roelkens, Gunther (In Optical Fiber Communication Conference, 2017)
Emerging applications such as high definition video streaming and cloud computing are the main drivers for the user-driven increase in the Internet traffic for the past few years. This has led to an increase in the processing capacity of the data centers demanding high-speed intra-datacenter communication links [1]. To address the expected growth of such short reach high speed links, the use of Wavelength Division Multiplexing (WDM) [2] and advanced modulation formats such as Quadrature Amplitude Modulation (QAM), multiband Carrierless Amplitude Phase Modulation (multi-CAP), Pulse Amplitude Modulation (PAM), and Discrete Multi-Tone (DMT) modulation [3,4] have been reported. Among these approaches, DMT has gained a lot of attention recently due to its ability to deliver 100G transmission using as low as ~20GHz optical devices [5]. Important considerations for such short reach communication links are low cost, small form factor and low power consumption. Silicon photonics is an emerging technology expected to deliver these attributes. Recently, data rates of 400 Gb/s by multiplexing 4 channels [5] and 0.88 Tb/s by multiplexing 10 channels [6] have been reported using silicon photonics. The power consumption of the optical frontend and footprint can be further reduced by implementing Directly Modulated Lasers (DMLs) on a heterogeneously integrated InP-on-Si platform [7]. Further more such lasers have been shown recently to have state-of-the-art modulation bandwidth performance [8]. In this paper we demonstrate single channel 69 Gb/s DMT modulation using a directly modulated heterogeneously integrated InP-on-Si DFB laser.